Bioprospection of filamentous fungi isolated from mangrove sediments of Pernambuco state for petroderivatives biodegradation (Research, Society and Development, 2022)
Activities involving the use of petroleum and its derivatives have been a cause of constant concern for the damage caused to ecosystems, due to the high toxicity and difficult degradation of these compounds. Consequently, several decontamination methods have been carried out, highlighting among them bioremediation, an ecologically viable technique that aims at the application of microorganisms and/or their products to remove or degrade petroleum derivatives and minimize the harmful effects in the impacted areas. In this sense, the use of microorganisms isolated from the ecosystem itself constitutes a promising strategy, considering that they already have mechanisms of resistance to these adverse environmental conditions. Thus, the aim of this work was to evaluate the biodegradation potential of petroderivatives of filamentous fungi isolated from mangrove sediments in the State of Pernambuco, contaminated with the spill that occurred in August 2019 on the coast of Northeast Brazil. For this, four fungal isolates belonging to the genera Aspergillus sp., Penicillium sp., Talaromyces sp. and Trichoderma sp. were subjected to acclimatization in Sabouraud Agar medium containing 1-20% of burnt engine oil, and growth was verified at all concentrations after 72 h. Then, the microorganisms acclimated to 20% were selected for the diesel and kerosene biodegradation test, in Bushnell Haas medium containing the redox indicator 2,6-dichlorophenol-indophenol (DCPIP), obtaining results above 75% after 72 h. However, Aspergillus sp. demonstrated the greatest potential, since it reached 88.4% of biodegradation of both petroderivatives. Thus, it is suggested the use of this promising microorganism in bioremediation processes of ecosystems impacted by oil and derivatives.